DEVELOPMENT OF CHARACTER-BASED LEARNING DEVICES FOR ELEMENTARY SCHOOL GRADE IV - Faeza Rezi S; Yuafriza Fadly (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
Education is the key in developing the nation's civilization. Every educational and learning process carried out is expected to instill good character in each student. Efforts to implement character education in the development of future society are a challenge for the world of education in Indonesia. Education will be the key to the progress of the nation's civilization in stemming the moral degradation it is experiencing. Character education has a higher meaning than moral education. Character education is not only related to the problem of right and wrong, but how to instill habits about the good things in life, so that students have high awareness and understanding, as well as concern and commitment to apply virtues in everyday life. This type of research is included in the type of Research and Development (Research and Development). Research and development methods are research methods used to produce products and test the effectiveness of certain products. To be able to produce certain products, research that is needs analysis is used and to test the effectiveness of these products so that they can function properly. The development of character-based learning tools for SD Class IV which was developed using the 4-D development model (four D Models), namely define, design, develop, and disseminate, the results are valid, practical and effective. Therefore it can be used as a learning guide for teachers and students at school.